Establishment of quality assurance in veterinary education: the Malaysian experience - Abdul Rahman, Sheikh Omar; Iskandar, Che Teh Fatimah Nachiar; Abdul Aziz, Saleha (Universiti Putra Malaysia Press, 2004)
The Faculty of Veterinary Medicine, Universiti Putra Malaysia embarked on a journey in 1999 to have all its core business processes certified through the Malaysian Standard (MS) ISO 9001 Quality Management System. The core processes comprised the undergraduate and postgraduate teaching, research, veterinary hospital, consultancy, continuing education and support services. This was a serious attempt by the Faculty to put in place quality assurance especially in the offering of the Doctor of Veterinary Medicine (DVM) programme. The Faculty was successful in the attempt and was subsequently awarded by SIRIM QAS Sdn. Bhd with the MS ISO 9001: 1994 certificate in July 2000 and with MS ISO 9001: 2000 in July 2003. This paper describes in some details the journey towards the certification and what is to follow in expediting the evolution of a quality culture in the Faculty as stipulated explicitly in its Quality Policy.